Morphological and Morphometrical Study of the Stink Bug Mustha spinulosa (Lefebrve, 1831) (Hemiptera: Pentatomidae) from Erbil – Iraq - Muhammed , Sarkaut Hussein; Ali , Wand Khalis (Iraqi Journal of Science, 2021)
All life stages of the pentatomid stink bug Mustha spinulosa (Lefebrve, 1831) (Hemiptera: Pentatomidae) collected from several types of trees in Erbil Governorate, North Iraq, along with their morphometrical description, were illustrated. Eggs are barrel in shape, green in color when freshly laid, and usually deposited in clusters that contain 14 eggs each (sometimes 12). Nymphs complete their stage through 5 instars. Head, pronotum, and connexivum of the adults and instars are with pale pink and gray spines; female is slightly larger than male; female is 27.30 mm long and 12.80 mm wide, while male is 25.80 mm long and 11.98 mm wide. Labium proboscis is1.25 ± 0.01 cm long, with brown blackish color. A pair of scent glands are located on the underside of thorax between second and third leg base. All body parts, especially head, thorax, and abdomen are densely covered with setae.